Penyuluhan Dan Pendampingan Terapi Massage Pada Ibu Hamil Untuk Mengatasi Kecemasan Dalam Kehamilan Trimester Iii Di Kabupaten Buukumba: Penyuluhan Dan Pendampingan Terapi Massage Pada Ibu Hamil Untuk Mengatasi Kecemasan Dalam Kehamilan Trimester Iii Di Kabupaten Buukumba - Erniawati Erniawati; Jusni Jusni; Fitriana Ibrahim; Arfiani Arfiani; Ariani Ariani (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2023)
Pregnancy is an important period in a mother's life. When pregnant women experience high levels of anxiety, especially in the first and third trimesters, the body will produce the stress hormone cortisol. If excessive levels of this stress hormone can affect the baby's health because it can enter the amniotic fluid through the placenta. Post partum depression occurs within 3-6 months, 13%-22% is caused by depression that occurs in the third trimester of pregnancy. Overcoming anxiety problems can include pharmacological and non-pharmacological therapy. One non-pharmacological therapy that can overcome anxiety in pregnant women is massage. Massage is a type of therapy that involves touching or light massage which is very important for pregnant women. Massage therapy is a non-pharmacological therapy option that can be applied to pregnant women to increase comfort for pregnant women. This community service activity is applied to pregnant women who live in Bontobulaeng Hamlet, Padang Village, Kab. Bulukumba. This activity uses the practical method of giving massage to pregnant women using the homecare service method. Implementation time is September 2023. The target is 5 pregnant women with a gestational age of 20 – 35 weeks. This activity has an impact on the community, especially pregnant women who feel more comfortable after being given massage therapy for approximately 60 minutes. This is proven by the reduction in physical complaints currently felt and the increase in sleep quality of pregnant women Key words: Pregnancy, Anxiety, Massage Therapy